"Interferent Detect" on the Intoxilyzer® 8000C in an individual with an elevated blood acetone concentration due to ketoacidosis. Issue 4 (2nd October 2017) - Wallage, H. Rachelle; Bugyra, Inger M.
ABSTRACT: A 72-year-old male was arrested for impaired driving. He had a history of chronic alcohol 1 consumption and limited food intake on the day of his arrest. The Intoxilyzer® 8000C provided the following communication messages during testing: "Interferent Detect", "Invalid Sample" and then an additional "Interferent Detect." This information from the Intoxilyzer® 8000C prompted a medical investigation. The individual was taken to the hospital where ketoacidosis was part of the medical diagnosis. Blood samples were collected and analyzed at two hospital laboratories and the Centre of Forensic Sciences. The results from the hospital analyses were serum ethanol concentrations of 172 and 161 mg/100 mL and an acetone concentration of 18 mg/100 mL; the results from the forensic analyses were blood ethanol, acetone, isopropanol and beta-hydroxybutyrate concentrations of 139 mg/100 mL, 21 mg/100 mL, <5 mg/100 mL and 468 mg/L, respectively.